Fluctuating asymmetry of some head structures and its possible causes - Żądzińska, Elżbieta (Polskie Towarzystwo Antropologiczne, 2003)
The analysis of eight cephalometric paired characters of 1236 children aged 7 to 10 was carried out. The standarized variance of differences between right and left values of same individuals were used to assess the fluctuating asymmetry (FA) level of each character and each individual. The highest values of FA were observed for the width of the wings of the nose (ala) (al-sn) and for the lenght of the nostrils (na-np), and the lowest for the length of the auricle (sa-sba) and length of the mandibular body (go-gn). Using the multiple regression the associations between the FA of the head and characterisics of individuals at birth as well as selected prenatal factors were estimated. These variables as a complex explain about 8% of the FA variability. Heavier newborns with bigger head and smaller chest circumference are characterized by more symmetric faces. Among the analyzed prenatal factors the declared alcohol consumption by the mother and smoking cigarettes by the father increased the FA level of a child's head.
Keywords: developmental stability; cephalometry; prenatal factors